Clinical risk factors of acute severe or fatal violence among forensic mental health patients. (May 2019) - Chan, Billy; Shehtman, Maria
Highlights: Some psychotic symptoms were proximal risk factors of severe or fatal violence. Family members were more likely to be a victim of acute severe or fatal violence. Substance use and gender did not associate with acute severe or fatal violence. Abstract: Existing violence risk assessment studies of mental health patients focus mostly on the association of historical presence of clinical risk factors and long-term violence, with little emphasis on the short-term temporal proximity between clinically relevant risk factors and the occurrence of violent behaviors. This research examined the proximal clinical risk factors (within days to a week prior) of acute severe or fatal violence among a group of forensic patients with serious mental illness ( N  = 287) found Not Criminally Responsible for offenses that involved violence against person(s), based on file review. Command hallucinations (OR  =  2.35, 95% CI  =  1.05 – 5.24), Threat/control-override symptoms (OR  =  3.10, 95% CI  =  1.51 – 6.35) and Capgras syndrome (OR  =  3.58, 95% CI  =  1.06 – 12.15) were identified as independent significant risk factors associated with acute severe or fatal violence. First degree relatives and intimate partners were significantly associated with being a victim of acute severe or fatal violence. Gender, recent alcohol use and recent drug use were not significantly associated with acute severe or fatal violence. Clinical utilities of the results and future directions for research are discussed.